Theoretical and Experimental Investigation of Transient Temperature Distribution in Friction Stir Welding of AA 7020-T53 (Journal of Engineering, 2012)
Finite element modeling of transient temperature distribution is used to understand physical phenomena occurring during the dwell (penetration) phase and moving of welding tool in friction stir welding (FSW) of 5mm plate made of 7020-T53 aluminum alloy at 1400rpm and 40mm/min.Thermocouples are used in locations near to the pin and under shoulder surface to study the welding tool penetration in the workpiece in advance and retreate sides along welding line in three positions (penetrate (start welding) , mid, pullout (end welding)).Numerical results of ANSYS 12.0 package are compared to experimental data including axial load measurements at different tool rotational speeds (710rpm.900rpm.1120rpm and 1400rpm) Based on the experimental records of transient temperature at several specific locations of thermocouples during the friction stir welding process the temperatures are higher on the advancing side (629.2 oK) than the retreating side (605 oK) along welding line and temperature in the top of workpiece under tool shoulder is higher(645 oK) than bottom (635.79oK). The results of the simulation are in good agreement with that of experimental results. The peak temperature obtained was 70% of the melting point of parent metal.